Teaching public health in undergraduate medical courses: a case study in three universities in Paraná - Campos, João José Batista de; Elias, Paulo Eduardo Mangeon; Cordoni Junior, Luiz (São Paulo Medical Journal, 2009)
CONTEXT AND OBJECTIVE: Historically, different concepts of public health have influenced both the specific teaching in this field and its participation in general physician training. Starting from this assumption, the objective of this paper was to study how public health has been taught in undergraduate medical courses, focusing on structure and on how this has affected curriculum design in three universities in the State of Paraná, Brazil. DESIGN AND SETTING: Qualitative investigation developed at Universidade Federal do Paraná (UFPR), Universidade Estadual de Londrina (UEL) and Universidade Positivo (UnicenP). METHODS: This study included a documentary analysis on pedagogical projects and on how these are actually experienced by those working on them. Eleven managers and 18 teachers were interviewed, as well as four groups of students that were formed in the three medical courses. RESULTS: Between 5 and 20% of Public Health topics were shown to be included in the curriculums, depending on the teaching strategies used. However, they were always set up within academic approaches that were strongly linked to healthcare services. This situation has been strengthened through the degree of progress made by the National Health System (Sistema Único de Saúde, SUS) in both cities (Curitiba and Londrina). CONCLUSIONS: Regardless of the nature of the university, the administrative and academic setup of the course and of the different ways of incorporating teachers, Public Health is present and takes on considerable relevance for medical training, even if it does not constitute a linking thread within undergraduate medical courses.